THE KINETICS OF PRECIPITATE COARSENING IN ZIRCALOY-2 - Harini Sosiati; Sungkono Sungkono (Jurnal Sains Materi Indonesia, 2000)
THE KINETICS OF PRECIPITATE COARSENING IN ZIRCALOY-2. Zircaloy-2 has been used as fuel element cladding material in both light and heavy water power reactors. The aims of the experiment are to study the kinetics of precipitate coarsening during isothermal a-annealing and to characterize the nucleation and growth of precipitate affected by the variations of cold work and heat treatment. The results of the experiment show that all specimens annealed at 650°C have the average precipitate diameter less than 0.1 um whereas those at 750°C have the average size larger than 0.1 .tm except for one annealed for less than 5 hours. The average size of precipitates is 0.07 um for specimens deformed before 0-quenching and 0.168 .tm for specimens deformed after 0-quenching. The deformed specimens after 13-quenching have more homogeneous size distribution than that of undeformed specimens and specimens deformed before 0-quenching. The kinetics of precipitate coarsening depends on the changes in annealing temperature and time, and cooling rate from the 0-phase region. The nucleation and growth of precipitates have been influenced by the variations of cold work and heat treatment.